Pengaruh Likuiditas Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Rokok Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2013-2022 - Walangadi, Moh Ikram; Rasjid, Hartelina; Amali, Lanto Miriatin (Universitas Gorontalo, 2024)
AbstractThis research aimed to determine the extent of the influence of liquidity using the Current Ratio (CR) proxy andThis research aimed to determine the extent of the influence of liquidity using the Current Ratio (CR) proxy and profitability with the Net Profit Margin (NPM) proxy on stock price, both partially and simultaneously. The study focused on three samples of tobacco companies listed on the Indonesia Stock Exchange during the 2012 to 2021 period. The sumpling method employed was purposive sampling and the data utilized were secondary. The data analysis method involved multiple linear regression analysis, as well as partial and simultaneous tests. The result indicated that, partiallty, the net profit margin had a positive and significant effect on stock prices, while the current ratio, on the other hand, did not have a significant impact on stock prices. Simultaneously, both the current ratio and net profit margin had a significant impact on stock prices.